Het betwiste landschap van de Haarlemmermeer - E. Taverne (BMGN: Low Countries Historical Review, 2006)
Ed Taverne, The controversial landscape of the Haarlemmermeer In the context of this article, ‘controversial landscape’ refers to the rather bad reputation of the reclamation of the Haarlemmermeer (1851): one of the greatest technical projects in the Netherlands during the nineteenth century. From the very moment this new polder had fallen dry, the project was severely criticized for its lack of social order and its unsatisfactory landscape. A succession of different groups beginning with the artists of the so-called ‘Hague School’, followed by the activists of the nature conservation movement around 1900 and eventually the town and country planning advocates in the 1920s, considered the creation of this rational agricultural landscape to be a regrettable break with the rich tradition of Dutch landscape architecture. Indirectly, these criticisms influenced the spatial and social layout of the new IJsselmeerpolders from the early 1920s and paved the way after the Second World War for the model of the future development of the Dutch national territory: Randstad Holland. This article is part of the special issue 'Landschap, natuur en nationale identiteit'.